Efeito da aeração intermitente e da temperatura no processo de nitrificação parcial/anammox para pós-tratamento de digestato de resíduos alimentares - Brenda Gonçalves Piteira Carvalho (2019)
Anaerobic biodigestion of food waste, methanization, is a robust and efficient process to divert food wastes from landfills, as well as the potential to produce energy (from biogas). However, the digestate from this process is highly concentrated in terms of several components, including organic and ammoniacal nitrogen. Therefore, strategies for the management of these nutrients have been investigated for the treatment of wastewater. Among these processes, the partial nitrification/anammox process (PN/A) is very interesting, having advantages from a sustainable, efficient and economical perspective. However, this process is limited by several factors, specially aeration and temperature conditions. Thus, this work investigated different intermittent aeration strategies and operation under optimal temperature (35 °C) and room temperature (26-29 °C) to establish PN/A in a sequencial batch reactor (SBR) applied to the treatment of anaerobic effluent from food waste (digestate). It was verified that the best aeration strategy at 35 °C (aerobic/anaerobic periods of 7min/14min and oxygen application rate of 0.050 L/min.L) had median removal efficiencies of N-NH4+ and total nitrogen of 81 and 63%, respectively. Adicionally, the median loads removed of N-NH4+ and total nitrogen were 76 and 67 g/m³.d, respectively. This values were higher than others previously reported in PN/A for food waste digestate treatment. Under the best aeration intermittent condition, the SBR operating at room temperature did not affect the performance system. The median N-NH4+ and total nitrogen removal efficiencies were 86 and 71%, respectively, with median N-NH4+ and total nitrogen loads removed of 77 and 51 g / m³.d, respectively. Comparing there results with the phase under 35 °C, there was no significative difference between the efficiencies removal and N-NH4+ and total nitrogen loads removed. The high concentrations of organic matter and solids had no negative effect on the PN/A process performance. The dominant anammox genus was Candidatus Brocadia, which was gradually replaced by Candidatus Jettenia. This study proved that through optimization of control parameters of PN/A systems, it is possible to achieve good performance conditions and high nitrogen removal efficiencies from food waste digestate in SBR.